Magnetic Nanoparticles PCR Enzyme‐Linked Gene Assay for Quantitative Detection of BCR/ABL Fusion Gene in Chronic Myelogenous Leukemia. Issue 5 (14th December 2015) - Manthawornsiri, Yanaphat; Polpanich, Duangporn; Yamkamon, Vichanan; Thiramanas, Raweewan; Hongeng, Suradej; Rerkamnuaychoke, Budsaba; Jootar, Saengsuree; Tangboriboonrat, Pramuan; Jangpatarapongsa, Kulachart
Abstract : Background: Magnetic nanoparticles (MNPs) have been widely used in medical diagnostic research. In this work, two technologies, MNPs and polymerase chain reaction (PCR), were combined to increase detection sensitivity and specificity. A novel technique based on the MNPs‐PCR enzyme‐linked gene assay (MELGA) was developed for detection of the BCR/ABL abnormal gene in chronic myelogenous leukemia (CML) patients. Methods: An MNPs‐labeled BCR forward primer and a biotin‐labeled ABL reverse primer were used to specifically amplify the target gene. After magnetic separation, the PCR product bound to MNPs labeled with streptavidin‐conjugated horseradish peroxidase was incubated with the peroxidase substrate and hydrogen peroxide to generate the colorimetric signal. Results: When compared with real‐time quantitative‐PCR (RQ‐PCR), the MELGA technique exhibited an increased sensitivity of <1 fg with high specificity for the BCR/ABL fusion gene in CML patients. In addition, MELGA colorimetric results correlated well with the number of copies obtained from RQ‐PCR. Conclusion: This simple and cost‐effective technique is suitable for monitoring CML patients during targeted therapy (tyrosine kinase inhibitors) especially in rural hospitals.